The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21815/jde.018.037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Dental Faculty Members’ Perceptions of Diagnostic Errors and How to Avoid Them

Abstract: Diagnostic errors are increasingly recognized as a source of preventable harm in medicine, yet little is known about their occurrence in dentistry. The aim of this study was to gain a deeper understanding of clinical dental faculty members' perceptions of diagnostic errors, types of errors that may occur, and possible contributing factors. The authors conducted semi-structured interviews with ten domain experts at one U.S. dental school in May-August 2016 about their perceptions of diagnostic errors and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Further, this finding is supported by previous studies where delays in referral by clinicians are a huge contributing factor to delayed diagnosis of oral cancer [ 20 , 28 , 29 ]. Oral cancer and periodontal diseases were also on the top of the missed and delayed diagnosed dental conditions reported by Nikdel et al [ 7 ]. Regression analysis showed that Al-Azhar and Governmental universities staff reported that oral mucosal lesions were the most diagnostic errors conditions followed by pulp therapy related conditions, disagreeing with the staff of Private universities who reported the pulp therapy related conditions to be the most common diagnostic errors conditions, more data regarding various aspects related to teaching and assessment methods and the contents of both subjects is needed to explain this observation.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Further, this finding is supported by previous studies where delays in referral by clinicians are a huge contributing factor to delayed diagnosis of oral cancer [ 20 , 28 , 29 ]. Oral cancer and periodontal diseases were also on the top of the missed and delayed diagnosed dental conditions reported by Nikdel et al [ 7 ]. Regression analysis showed that Al-Azhar and Governmental universities staff reported that oral mucosal lesions were the most diagnostic errors conditions followed by pulp therapy related conditions, disagreeing with the staff of Private universities who reported the pulp therapy related conditions to be the most common diagnostic errors conditions, more data regarding various aspects related to teaching and assessment methods and the contents of both subjects is needed to explain this observation.…”
Section: Discussionmentioning
confidence: 95%
“…Two of our study participants were teaching staff at the bio-dental materials department, which is an academic department, however, they do have a private clinic. General dentists were excluded in accordance with Nikdel et al, 2018 as dentists in dental centers or private offices who experience an error-in the best of cases, they learn from it, but in most cases, they will try to conceal it from other professionals [ 7 ]. This means that a bulk of information on errors will be lost and cannot be properly studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations